Etnofotografi Kesenian Wayang Krucil - Fariza Wahyu Arizal (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This ethnophotography book of Wayang Krucil Malang is an idea about the importance of information, documentation and one of the efforts to protect and maintain art and culture in Malang Raya. Currently Wayang Krucil in Gondowangi Village is in a poor condition, not many people care about this art, except for only a few artists. Concern from the government is also felt to be very lacking, when in fact this Krucil Puppet can be used as an artistic and cultural asset in Malang Raya. In this design, photography is used as a method to analyze a culture in everyday life. The focus of the design of this book is more on the visual aspect using photography as the medium. The selection of photography is considered capable of displaying the reality of the social situation in it. Photos recorded on the camera can display a variety of information and materials about ethnography. Ethnophotography comes from the amalgamation of ethnography and photography in anthropological studies. With the design of this book, it is hoped that it will be able to provide information to the public about the art of Wayang Krucil and can foster a sense of love, ownership and preservation of existing cultural arts. Keywords: etnophotography, art, wayang krucil Abstrak: Buku etnofotografi Wayang Krucil Malang-an ini adalah gagasan tentang pentingnya informasi, dokumentasi serta salah satu upaya untuk melindungi dan menjaga seni dan budaya di Malang Raya. Saat ini Wayang Krucil di Desa Gondowangi dalam kondisi yang cukup memprihatinkan, tidak banyak orang yang peduli dengan kesenian ini, kecuali hanya beberapa seniman saja. Kepedulian dari pihak pemerintahan juga dirasa masih sangat kurang, padahal sebenarnya Wayang Krucil ini dapat dijadikan aset seni dan budaya di Malang Raya. Dalam perancangan ini fotografi digunakan sebagai metode untuk menganalisis sebuah kebudayaan dalam kehidupan sehari-hari. Perancangan buku ini dititik beratkan pada segi visual yang menggunakan foto sebagai medianya. Pemilihan Fotografi dianggap mampu menampilkan realitas situasi sosial didalamnya. Foto yang terekam dalam kamera dapat menampilkan beragam informasi serta materi tentang etnografi. Etnofotografi adalah penggabungan antara etnografi dan fotografi dalam studi antropologi. Dengan adanya perancangan buku ini agar dapat memberikan informasi kepada masyarakat mengenai kesenian Wayang Krucil serta dapat menumbuhkan rasa kecintaan terhadap kesenian dan budaya yang ada. Kata kunci: etnofotografi, kesenian, wayang krucil